INFORMATION AS A KEY TO UNDERSTANDING THE SUBJECT’S SITUATION AND POTENTIAL - Kaluha , Volodymyr (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Every thinking being strives for equilibrium, yet development presupposes transformation and tension. This generates a cognitive contradiction between stability and change, producing a need to clarify the principles of existence and the subject’s orientation within it. Information is considered as a key factor in understanding this situation. The aim and tasks. The article aims to systematize the understanding of information as a basic element of being, particularly in its social dimension. The tasks include: (1) analysis of the human epistemic situation with regard to the capacity for self-cognition; (2) critical examination of the key interpretations of information; (3) investigation of the probable structure of information and the functional load of its states; (4) systematization of the resulting ideas and articulation of the key principles of informational existence. Research methods. The study is speculative in nature and is based on a combination of speculative method, hermeneutics, comparative analysis, deduction, and induction. The principle of correspondence between thought and experience serves as a methodological constraint. Research results. Three approaches to information are distinguished: philosophical-ontological, mathematical, and integrative. An axiomatically grounded model is proposed in which the activation of a primordial unmanifest potential generates Being, Consciousness, and Energy, the last of which manifests as Information – a continuum and carrier of meanings. Three states of information are identified – deep (integrative), digital, and representational – with their corresponding means of recording and circulation: knowledge, matrices, and representations respectively. Knowledge is directly linked to reality and practice; representations constitute the ground of any worldview and the space of social freedom and subjectivity. Discussion. Representations do not reproduce truth but constitute a field of stable determinacy for the thinking being. They may stimulate self-actualization or, conversely, dissolution into the mass. The institution that stands behind the formation of representations at the level of the subject in effect determines the character of his activity and priorities. Conclusions. Four conclusions correspond to the four tasks. First, the predominant state of the contemporary subject – "social anabiosis" – substantially limits adequate self-cognition and produces stereotypical worldviews. Second, three approaches to information are distinguished, none sufficient on its own. Third, three states of information are identified with their respective means of circulation; freedom is realized at the level of representations and the reality constituted by them. Fourth, awareness of the role of representations in shaping the subject’s activity is a necessary condition for revising the hierarchy of values and transitioning from superficial data-handling to an understanding of the deep informational nature of being.